Polarizing plate and optical display device
By adopting a specific retardation layer stacking structure in the polarizer, the problem of insufficient durability and reliability of the polarizer in high temperature and high humidity environments is solved, high impact resistance and good bending performance are achieved, and optical performance is improved.
Patent Information
- Application Number
- CN202411529125.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-31
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
AI Technical Summary
The existing polarizers lack durability and reliability in high temperature and high humidity environments, and their impact resistance and bending performance are poor, resulting in the continuous improvement of optical performance being difficult to achieve.
A retardation layer stack structure including a first adhesive layer and a second retardation layer is adopted. The energy storage modulus of the first adhesive layer is 1×105Pa to 1×106Pa at 25°C, and the thickness relationship between the second retardation layer and the first adhesive layer is 0.3≤T2/T1≤1.0, ensuring the durability and reliability of the polarizer in a high temperature/high humidity environment.
It realizes that the polarizer has good durability and reliability after being placed in high temperature/high humidity environment for a long time, has high impact resistance and good bending performance, while improving the front contrast and reducing the side brightness in black mode, reducing light leakage and color changes.
Smart Images

Figure CN119916518A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0148104, filed on October 31, 2023, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field
[0003] The present disclosure relates to a polarizing plate and an optical display device. Background Art
[0004] An organic light emitting device (OLED) or a liquid crystal display includes a polarizing plate to improve optical properties. The polarizing plate may include a single retardation layer or a retardation layer stack composed of two or more retardation layers. A polarizing plate including a retardation layer stack can ensure better optical property improvement than a polarizing plate including a single retardation layer. In order to ensure continuous improvement of optical properties (e.g., continuous optical performance), it is desirable that the polarizing plate has good durability and reliability.
[0005] The polarizing plate is usually arranged at the outermost part of the light emitting display device or the liquid crystal display. Therefore, it is desirable that the polarizing plate has good impact resistance, so that if (for example, when) the polarizing plate is exposed to external impact (for example, force), the delay layer of the delay layer stack will not suffer from fracture, cracking and / or depression.
[0006] Recently, there has been a growing interest in foldable optical displays, and therefore, it is desirable or required that the polarizing plate have excellent bending properties.
[0007] The background art of the present disclosure is disclosed in Korean Patent Publication No. 10-2013-0103595 and the like. Summary of the invention
[0008] One aspect according to some embodiments of the present disclosure relates to a polarizing plate having good durability and reliability even after being left at high temperature and high humidity (hereinafter referred to as high temperature / high humidity) or high temperature for a long time.
[0009] One aspect according to some embodiments of the present disclosure relates to a polarizing plate having high impact resistance.
[0010] One aspect according to some embodiments of the present disclosure relates to a polarizing plate with good bending performance.
[0011] One aspect according to some embodiments of the present disclosure relates to a polarizing plate that can provide good front contrast and reduce side brightness in a black mode to reduce side light leakage and color changes.
[0012] Additional aspects will be set forth in part in the description which follows and, in part, will be obvious from the description, or may be learned by practice of the embodiments presented in the disclosure.
[0013] One aspect of the present disclosure relates to a polarizing plate.
[0014] According to one or more embodiments of the present disclosure, the polarizing plate includes: a polarizer having a first surface and a second surface facing the first surface; and a delay layer stack located on the first surface of the polarizer, wherein the delay layer stack includes a second delay layer, a first adhesive layer, and a first delay layer stacked in sequence from the first surface of the polarizer, and the storage modulus of the first adhesive layer at 25° C. is 1×10 5 Pa to 1×10 6 Pa, and the second retardation layer and the first adhesive layer satisfy the relationship 1:
[0015] [Relation 1]
[0016] 0.3≤T2 / T1≤1.0
[0017] where T1 is the thickness of the first adhesive layer in micrometers, and
[0018] T2 is the thickness of the second retardation layer in microns.
[0019] Another aspect of the present disclosure relates to an optical display device.
[0020] According to an embodiment of the present disclosure, an optical display device includes the polarizing plate as described above.
[0021] Embodiments of the present disclosure provide a polarizing plate having good durability and reliability even after being left in a high temperature / high humidity or high temperature environment for a long time.
[0022] Embodiments of the present disclosure provide a polarizing plate having high impact resistance.
[0023] Embodiments of the present disclosure provide a polarizing plate with good bending performance.
[0024] Embodiments of the present disclosure provide a polarizing plate that can provide good front contrast and can reduce side brightness in a black mode to reduce side light leakage and color changes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings are used to further understand the present disclosure and are incorporated into and constitute a part of the present specification. The accompanying drawings illustrate embodiments of the present disclosure and together with the specification are used to explain the principles of the present disclosure. In the accompanying drawings,
[0026] Figure 1 is a cross-sectional view of a polarizing plate according to one or more embodiments of the present disclosure.
[0027] Figure 2 is a cross-sectional view of a polarizing plate according to another embodiment of the present disclosure.
[0028] Figure 3 is a cross-sectional view of a polarizing plate according to yet another embodiment of the present disclosure.
[0029] Figure 4 It is a schematic diagram of impact resistance evaluation.
[0030] Description of Figure Numbers
[0031] 1: First support;
[0032] 2: Second support;
[0033] 3: Soda lime glass;
[0034] 4: Cut polarizing plate samples;
[0035] 100:Polarizer;
[0036] 210: first delay layer;
[0037] 220: second delay layer;
[0038] 230: first adhesive layer;
[0039] 300: first protective layer;
[0040] 400: second adhesive layer;
[0041] 500: second protective layer;
[0042] 600: the third adhesive layer. DETAILED DESCRIPTION
[0043] Hereinafter, exemplary embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. However, it should be understood that the present disclosure is not limited to the following embodiments and can be implemented in different ways. The following embodiments are provided to enable those skilled in the art to fully understand the present disclosure. Although the length, thickness or width of various components may be exaggerated in the accompanying drawings for the purpose of describing the present disclosure, the present disclosure is not limited thereto. Throughout the accompanying drawings, the same components will be represented by the same reference numerals.
[0044] The terms used herein are intended to describe exemplary embodiments rather than to limit the present disclosure.Herein, the singular forms "a", "an", and "the" are intended to include the plural forms, unless the context specifically indicates otherwise.
[0045] Here, spatially relative terms such as "on" and "under" are defined with reference to the accompanying drawings. Therefore, it is understood that "upper surface" can be used interchangeably with "lower surface". In addition, if (for example, when) an element is referred to as being "on" another element, it can be directly placed on the other element, or there may be intervening elements. On the other hand, if (for example, when) an element is referred to as being "directly on" another element, there are no intervening elements between them.
[0046] Here, "in-plane retardation (Re)", "out-of-plane retardation (Rth)", and "degree of biaxiality (NZ)" are represented by equations A, B, and C, respectively:
[0047] Re=(nx-ny)×d, ---(A)
[0048] Rth=((nx+ny) / 2-nz)×d, ---(B)
[0049] NZ=(nx-nz) / (nx-ny), ---(C)
[0050] Where nx, ny and nz are the refractive indices measured by the optical device along the slow axis direction (nx), fast axis direction (ny) and thickness direction (nz) at the measurement wavelength, respectively, and d is its thickness (unit: nanometer).
[0051] In equations A to C, the term "optical device" may refer to a first retardation layer, a second retardation layer, a protective layer, or a retardation layer stack. In equations A to C, the term "measurement wavelength" may represent a wavelength of 450 nanometers, 550 nanometers, or 650 nanometers.
[0052] Herein, the term "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0053] Here, the term "glass transition temperature" of a layer (e.g., the first adhesive layer, the first delay layer, and the second delay layer) can be measured by differential scanning calorimetry (DSC). For example, the glass transition temperature is a value obtained by measuring a sample by heating the sample to 180°C at a heating rate of 20°C / min in a nitrogen atmosphere (flow rate of 50 ml / min) using Discovery (TA Instrument Inc.), then cooling the sample to -100°C, and heating the sample again to 100°C at a heating rate of 10°C / min, wherein the sample is prepared from 15 mg each of the first adhesive layer, the first delay layer, or the second delay layer (on a 6 mm aluminum pan).
[0054] Here, the term "modulus" of an adhesive layer (e.g., a first adhesive layer and a second adhesive layer) refers to a storage modulus. The storage modulus is a value obtained by measuring a sample at 25°C and 60°C using a storage modulus measuring instrument ARES (Advanced Rheometry Expansion System (ARES), TA Instrument Inc.) while heating the sample from 0°C to 100°C (heating rate: 10°C / min), wherein the sample is prepared by stacking the first adhesive layer or the second adhesive layer to form a laminate having a thickness of 500 μm and cutting the laminate into a circle having a diameter of 8 mm.
[0055] Here, the term "water vapor permeability" of the delay layer refers to a value measured at 23°C and 99% to 100% relative humidity (RH). The water vapor permeability can be measured in a water vapor permeability measuring instrument (PERMATRAN-W, Model 700) on a sample prepared by cutting the delay layer into a size of 10 cm x 10 cm (length x width). Here, the "water vapor permeability" of the protective layer can also be measured in the same manner as the delay layer.
[0056] Here, the wavelength dispersion values of the in-plane retardation at wavelengths of 450 nm, 550 nm, and 650 nm are represented by Re(450) / Re(550), Re(550) / Re(550), and Re(650) / Re(550), respectively.
[0057] Here, the wavelength dispersion values of out-of-plane retardation at wavelengths of 450 nm, 550 nm, and 650 nm are represented by Rth(450) / Rth(550), Rth(550) / Rth(550), and Rth(650) / Rth(550), respectively.
[0058] When used herein to express a specific numerical range, “X to Y” means “greater than or equal to X and less than or equal to Y (X≤ and≤Y)”.
[0059] According to one or more embodiments, the polarizing plate includes a polarizer; and a delay layer stack formed on one surface of the polarizer, wherein the delay layer stack includes a second delay layer, a first adhesive layer, and a first delay layer stacked in sequence from one surface (e.g., the first surface) of the polarizer.
[0060] According to one or more embodiments, a polarizing plate having good durability and reliability even after being placed at high temperature / high humidity or high temperature for a long time is provided. For example, after the polarizing plate is placed at high temperature / high humidity or high temperature for a long time, the polarizing plate can prevent or substantially prevent the delay layers (i.e., the first delay layer and the second delay layer) constituting the delay layer stack from being separated by physical force. Here, the term "physical force" refers to a force applied by hand, such as forcibly separating the first delay layer and the second delay layer from each other by hand.
[0061] According to one or more embodiments, a polarizing plate having good impact resistance is provided. For example, if (e.g., when) an external impact is applied to the polarizing plate from the polarizer side, the polarizing plate can prevent or substantially prevent each delay layer (e.g., the second delay layer) constituting the delay layer stack from breaking, cracking, and / or being depressed (e.g., becoming indented). Here, the term "external impact" can refer to an impact, for example, applied by dropping an object from a set or predetermined height onto the polarizing plate.
[0062] According to one or more embodiments, a polarizing plate for increasing front contrast is provided. In addition, the polarizing plate according to the embodiment also provides the effect of reducing side light leakage and color change while ensuring good clarity on a black screen. Further, the polarizing plate according to the embodiment also provides a good (e.g., wide) viewing angle.
[0063] As will be described in more detail below, a retardation layer stack may be disposed between the polarizer and the optical display panel. The polarizer reduces side light leakage and color variations while ensuring good clarity and good viewing angles on a black screen.
[0064] In one or more embodiments, the polarizing plate can be used as a viewing side polarizing plate or a light source side polarizing plate in a lateral electric field liquid crystal optical display (e.g., an in-plane switching (IPS) or fringe field switching (FFS) mode liquid crystal display). Here, the "viewing side polarizing plate" refers to a polarizing plate that emits light after receiving light emitted from a liquid crystal panel. In another embodiment, the polarizing plate can be used as an anti-reflection polarizing plate in a light-emitting device display (such as an OLED, etc.).
[0065] A polarizing plate according to one or more embodiments of the present disclosure will be described in more detail below.
[0066] Delay layer stacking
[0067] The retardation layer stack is disposed between the polarizer and the optical display panel.
[0068] With respect to internal light, the retardation layer stack may be stacked on the light exit surface of the polarizer (when the polarizing plate is a light source side polarizing plate) or the light incident surface of the polarizer (when the polarizing plate is a viewing side polarizing plate). Here, "internal light" may be light emitted from a backlight unit.
[0069] The retardation layer stack includes a second retardation layer, a first adhesive layer, and a first retardation layer which are sequentially stacked starting from the polarizer.
[0070] First adhesive layer
[0071] In one or more embodiments, the first adhesive layer may be directly formed on each of the first delay layer and the second delay layer. Here, "directly formed" means that no other adhesive layer and / or bonding layer is formed between the first delay layer and the first adhesive layer, and no other adhesive layer and / or bonding layer is formed between the second delay layer and the first adhesive layer.
[0072] The first adhesive layer has a 1×10 5 Pa to 1×10 6 Pa, and the second retardation layer and the first adhesive layer satisfy the following relationship 1. The first adhesive layer satisfies both the above modulus range and relationship 1, which ensures that the polarizing plate has good durability and reliability by preventing or substantially preventing the delamination of the first retardation layer and the second retardation layer even after being placed at high temperature / high humidity or high temperature for a long time, and means that if (for example, when) an external impact is applied to the polarizing plate, the second retardation layer will not break, crack and / or dent (for example, become indented).
[0073] 0.3 ≤ T2 / T1 ≤ 1.0, --- (1)
[0074] Wherein T1 is the thickness of the first adhesive layer (unit: μm), and T2 is the thickness of the second retardation layer (unit: μm).
[0075] The first adhesive layer adheres the second retardation layer and the first retardation layer to each other and is disposed on the lower surface of the second retardation layer to absorb the impact on the second retardation layer if (for example, when) an external impact is applied to the polarizer. The modulus of the first adhesive layer at 25°C is set in consideration of the peel strength of the first adhesive layer relative to the second adhesive layer and the impact resistance of the polarizing plate.
[0076] If (for example, when) the modulus of the first adhesive layer at 25°C is less than 1×10 5 Pa, the polarizing plate may have poor impact resistance. If (for example, when) the modulus of the first adhesive layer at 25° C. is greater than 1×10 6 When the polarizing plate has a modulus of 0.0447 W / cm2 and a modulus of 0.022 W / cm2, the polarizing plate may have poor impact resistance or low peel strength relative to the second retardation layer, thereby providing poor durability and reliability. If (for example, when) the second retardation layer is a non-liquid crystal layer (for example, the second retardation layer is not a liquid crystal layer and does not contain any liquid crystal material), the above-mentioned modulus range of the first adhesive layer at 25° C. may be desirable or advantageous for improving the durability and reliability of the polarizing plate, as described in more detail below. For example, the second retardation layer may be a cured product of a composition comprising at least one of a cellulose compound or a polystyrene compound.
[0077] In the embodiment, the modulus of the first adhesive layer at 25° C. is, for example, 1×10 5 Pa, 2×10 5 Pa, 3×10 5 Pa, 4×10 5 Pa, 5×10 5 Pa, 6×10 5 Pa, 7×10 5 Pa, 8×10 5 Pa, 9×10 5 Pa, 1×10 6 Pa, 2×10 5 Pa to 9×10 5 Pa, or 3×10 5 Pa to 8×10 5 Pa. Within these ranges, the polarizing plate can (eg, easily) achieve the above-mentioned effects, and the first adhesive layer can (eg, easily) be formed.
[0078] The modulus of the first adhesive layer at 25° C. can be achieved by adjusting the type or kind of the adhesive resin in the composition used for the first adhesive layer. For example, if (for example, when) the adhesive resin is a (meth)acrylic resin, the modulus of the first adhesive layer at 25° C. can be achieved by adjusting the type or kind and / or content (for example, amount) of each monomer in the monomer mixture forming the (meth)acrylic resin, and / or the type or kind and / or content (for example, amount) of the curing agent, and / or the degree of curing.
[0079] Relation 1 is set in consideration of the optical properties of the second retardation layer and the durability, reliability and impact resistance of the polarizing plate. As will be described in detail below, the second retardation layer is a +C (positive C) retardation layer and may have a set or predetermined thickness to provide an appropriate range of out-of-plane retardation. Relation 1 is set to ensure the out-of-plane retardation of the second retardation layer that provides a +C retardation layer (e.g., +C retardation effect) while improving the durability, reliability and impact resistance of the polarizing plate.
[0080] If T2 / T1 in Relationship 1 is less than 0.3, the second retardation layer may not provide (or be unable to provide) the target out-of-plane retardation, and the first adhesive layer may have a relatively thick thickness, thereby providing a thick polarizing plate and poor impact resistance. If T2 / T1 in Relationship 1 is greater than 1.0, the peel strength between the first adhesive layer and the second retardation layer may be reduced, and thus the polarizing plate may have poor properties in terms of durability, reliability, and impact resistance.
[0081] In an embodiment, the value of the polarizing plate calculated according to Relation 1 is 0.3 to 0.9, 0.4 to 0.9, 0.5 to 0.8, or 0.3 to 0.7. Within these ranges, the polarizing plate can (eg, easily) achieve the above effects, and the first adhesive layer can (eg, easily) be formed.
[0082] In one or more embodiments, the first adhesive layer may have a thickness of 13 μm or less, for example, greater than 0 μm and less than or equal to 13 μm, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 2 μm to 13 μm, 3 μm to 12 μm, or 2 μm to 5 μm. Within these ranges, the polarizing plate can (e.g., easily) satisfy Relation 1.
[0083] In one or more embodiments, the second retardation layer may have a thickness of 10 μm or less, for example, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, greater than 0 μm and less than or equal to 10 μm, or 2 μm to 8 μm. Within these ranges, the polarizing plate can (e.g., easily) satisfy Relation 1 and achieve a reduced thickness of the retardation layer stack.
[0084] Relationship 1 can be achieved (or satisfied) by adjusting the thicknesses of the first adhesive layer and the second retardation layer in the polarizing plate.
[0085] In one or more embodiments, the modulus of the first adhesive layer at 60° C. may be 6×10 4 Pa to 8×10 5 Pa, for example, 6×10 4Pa, 7×10 4 Pa, 8×10 4 Pa, 9×10 4 Pa, 1×10 5 Pa, 2×10 5 Pa, 3×10 5 Pa, 4×10 5 Pa, 5×10 5 Pa, 6×10 5 Pa, 7×10 5 Pa, 8×10 5 Pa, or 8×10 4 Pa to 6×10 5 Pa, which is lower than the modulus of the first adhesive layer at 25° C. Within these ranges, the polarizing plate can ensure better durability and reliability after being in a high temperature / high humidity or high temperature environment for a long time.
[0086] In one or more embodiments, the first adhesive layer may have a modulus ratio (modulus at 25° C.: modulus at 60° C.) of 1.25:1 to 1.6:1. Within these ranges, the polarizing plate may ensure good durability and reliability over a wide temperature range.
[0087] In one or more embodiments, the first adhesive layer may have a glass transition temperature of -10°C or less, for example, -60°C to -10°C, or -50°C to -15°C. Within these ranges, the first adhesive layer may (eg, easily) achieve the above-mentioned modulus range.
[0088] In one or more embodiments, the first adhesive layer may be a pressure sensitive adhesive (PSA) layer.
[0089] As long as the first adhesive layer can provide the above-mentioned modulus range, the first adhesive layer can be formed by any suitable composition. For example, the first adhesive layer can be formed by a composition comprising at least one adhesive resin selected from (meth) acrylic acid, epoxy, epoxy (meth) acrylic acid, carbamate, carbamate (meth) acrylic acid and silicone resin. For example, the first adhesive layer can include a heat-cured product of the composition and / or a light-cured product of the composition.
[0090] In one or more embodiments, the first adhesive layer may include a thermally cured product of a composition containing a (meth) acrylic resin. The (meth) acrylic resin can be obtained (e.g., easily) as a monomer and can promote the formation of the adhesive layer. The following is a more detailed description of the composition containing a (meth) acrylic resin as an example.
[0091] The composition includes a (meth)acrylic resin.
[0092] The (meth)acrylic resin may include a (meth)acrylic copolymer including a monomer mixture of a (meth)acrylic monomer including an alkyl group and a (meth)acrylic monomer including a cross-linkable functional group.
[0093] The (meth)acrylic acid monomer containing an alkyl group may include a linear or branched C1 to C 20 Alkyl (meth)acrylate. For example, the (meth)acrylic acid monomer containing an alkyl group may include at least one monomer selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate, but is not limited thereto.
[0094] The (meth)acrylic monomer containing a crosslinkable functional group may include at least one monomer selected from a (meth)acrylic monomer containing a hydroxyl group, a (meth)acrylic monomer containing a carboxyl group, a (meth)acrylic monomer containing an amino group, and a (meth)acrylic monomer containing an epoxy group.
[0095] The hydroxyl-containing (meth)acrylic acid monomer may include a C1 to C2 monomer having at least one hydroxyl group at its ester site. 20 Alkyl (meth)acrylate. For example, the hydroxyl-containing (meth)acrylic monomer may include at least one monomer selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate.
[0096] The (meth)acrylic monomer containing a carboxyl group may include (meth)acrylic acid and / or the like.
[0097] The amino group-containing (meth)acrylic monomer may include a C1 to C2 amino group having a primary amine group (NH2), a secondary amine group (NH2), or a tertiary amine group (N2). 20 Alkyl (meth)acrylates. For example, the amino group-containing (meth)acrylic monomer may include dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, etc., but is not limited thereto.
[0098] The (meth)acrylic monomer containing an epoxy group may include a C1 to C2 monomer having an epoxy group at its ester site. 20Alkyl (meth)acrylate. For example, the epoxy group-containing (meth)acrylic monomer may include glycidyl (meth)acrylate and / or the like, but is not limited thereto.
[0099] In one or more embodiments, based on 100 wt% of the total amount of the monomer mixture, the monomer mixture may include 60 wt% to 99 wt% (e.g., 80 wt% to 95 wt%) of a (meth) acrylic monomer containing an alkyl group and 1 wt% to 40 wt% (e.g., 5 wt% to 20 wt%) of a (meth) acrylic monomer containing a crosslinkable functional group. Within these ranges, the (meth) acrylic resin may be (e.g., easily) prepared, and the adhesion of the first delay layer to the second delay layer may be improved.
[0100] The monomer mixture may further include a comonomer copolymerizable with the (meth)acrylic monomer containing an alkyl group and / or the (meth)acrylic monomer containing a crosslinkable functional group.
[0101] The comonomer may include at least one monomer selected from a (meth) acrylic monomer containing an aromatic group, a (meth) acrylic monomer containing an alicyclic group, and a (meth) acrylic monomer containing a heterocyclic group. Each of the (meth) acrylic monomer containing an aromatic group, a (meth) acrylic monomer containing an alicyclic group, and a (meth) acrylic monomer containing a heterocyclic group may be an appropriate monomer (e.g., a typical type known to those skilled in the art). Based on 100% by weight of the total amount of the monomer mixture, the content of the comonomer in the monomer mixture may be 30 wt% or less, for example, 0 wt% to 30 wt%.
[0102] The (meth)acrylic resin may have a weight average molecular weight of 500,000 g / mol to 3,000,000 g / mol, for example, 1,000,000 g / mol to 2,500,000 g / mol. The "weight average molecular weight" may be obtained by gel permeation chromatography using a polystyrene standard.
[0103] (Meth) acrylic resin can be prepared by polymerizing a monomer mixture by a suitable method (e.g., any typical method known to those skilled in the art). For example, (meth) acrylic resin can be prepared by solution polymerization, suspension polymerization, solid phase polymerization and / or similar methods.
[0104] The composition may further include a curing agent, such as a thermal curing agent.
[0105] The curing agent can cure the (meth) acrylic resin to increase the adhesion of the first adhesive layer. The curing agent can be selected and used according to the crosslinkable functional groups of the (meth) acrylic resin. For example, the curing agent can include at least one agent selected from an isocyanate curing agent, a metal chelate curing agent, an aziridine curing agent, an epoxy curing agent, and a carbodiimide curing agent. In an embodiment, the curing agent is a mixture of an isocyanate curing agent and a metal chelate curing agent.
[0106] The isocyanate curing agent may include a difunctional to hexafunctional isocyanate curing agent. Specifically, the isocyanate curing agent may include: at least one aromatic isocyanate curing agent selected from toluene diisocyanate, xylene diisocyanate, halogenated toluene diisocyanate, phenylene diisocyanate (including m-phenylene diisocyanate, etc.) and tetramethylxylene diisocyanate; at least one aliphatic isocyanate curing agent selected from hexamethylene diisocyanate and pentamethylene diisocyanate; alicyclic isocyanate curing agent, such as cyclohexamethylene diisocyanate, etc.; and / or its adducts, such as at least one polyol (such as trimethylolpropane (trimethylolpropan, TMP)) and the above curing agent. For example, the isocyanate curing agent may include an aromatic isocyanate curing agent, an aliphatic isocyanate curing agent, an alicyclic isocyanate curing agent, an adduct thereof, or a combination thereof.
[0107] According to one or more embodiments, the isocyanate curing agent may be included in an amount of 0.01 to 10 parts by weight (eg, 0.1 to 5 parts by weight) relative to 100 parts by weight of the (meth)acrylic resin. Within these ranges, the composition may ensure the above-described desired effects.
[0108] The metal chelate curing agent can be any suitable metal chelate curing agent. For example, the metal chelate curing agent can include a metal such as aluminum, titanium, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, zirconium and / or the like. For example, the metal chelate curing agent may include at least one selected from aluminum ethyl acetoacetatediisopropylate, aluminum tris(ethyl acetoacetate), aluminum alkyl acetoacetate aluminum diisopropylate, aluminum isopropylate, mono-sec-butoxyaluminum diisopropylate, aluminum sec-butyrate, aluminum ethoxide, tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, titanium acetylacetonate, titanium octylene glycolate, titanium tetraacetylacetonate, titanium ethyl acetoacetate, polyhydroxytitanium stearate, and aluminum acetylacetonate.
[0109] According to one or more embodiments, the metal chelate curing agent may be included in an amount of 0.01 to 10 parts by weight (eg, 0.01 to 3 parts by weight) relative to 100 parts by weight of the (meth)acrylic resin. Within these ranges, the composition may (eg, easily) achieve the above-described desired effects.
[0110] According to one or more embodiments, the curing agent may be included in an amount of 0.01 to 10 parts by weight (eg, 0.1 to 5 parts by weight) relative to 100 parts by weight of the (meth)acrylic resin. Within these ranges, the composition may (eg, easily) achieve the above-described desired effects.
[0111] The composition may further include an additive. The additive may include at least one agent selected from a silane coupling agent, an antistatic agent, a pigment, a dye, an ultraviolet absorber, a heat stabilizer, and an antioxidant. In one or more embodiments, the content of the silane coupling agent may be 0.01 to 10 parts by weight (e.g., 0.1 to 5 parts by weight) relative to 100 parts by weight of the (meth) acrylic resin. Within these ranges, the composition can (e.g., easily) achieve the above-mentioned desired effect.
[0112] In one or more embodiments, the modulus of the first adhesive layer can be achieved by adjusting the type or kind and / or content (e.g., amount) of the monomer mixture of the (meth)acrylic resin, the type or kind and / or content (e.g., amount) of the curing agent, and / or the like.
[0113] The first adhesive layer can be prepared by heat curing by an appropriate method (e.g., a method known to those skilled in the art). For example, the composition of the first adhesive layer can be prepared by depositing the composition onto a release film of a set or predetermined thickness and drying the composition at a set or predetermined temperature, for example, at 30° C. to 80° C. for 0.5 to 5 hours.
[0114] First delay layer
[0115] The first retardation layer is a +A (positive A) layer (nx>ny≒nz). If (for example, when) combined with a second retardation layer as a +C layer, the first retardation layer can be applied to IPS or FFS mode liquid crystal displays to promote contrast enhancement and field of view expansion while minimizing or reducing color changes.
[0116] The first retardation layer may have an Re of 100 nm to 160 nm at a wavelength of 550 nm. Within this range, if (for example, when) combined with the second retardation layer, the first retardation layer may be applied to an IPS mode liquid crystal display to promote contrast enhancement and field angle expansion while minimizing or reducing color changes. In an embodiment, the first retardation layer has an Re of 120 nm to 150 nm, for example, 120 nm to 130 nm.
[0117] The first retardation layer may have an Rth of 50 nm to 85 nm at a wavelength of 550 nm, for example 50 nm to 80 nm, or 55 nm to 70 nm. Within these ranges, the first retardation layer may (e.g., easily) achieve the above Re range.
[0118] The first retardation layer may have a biaxiality (NZ) of 0.9 to 1.1 at a wavelength of 550 nm, for example 0.95 to 1.05, or 1 to 1.02. Within these ranges, the first retardation layer may (eg, easily) achieve the above Re range.
[0119] The first retardation layer may have positive wavelength dispersion (Re(450)>Re(550)>Re(650)) or flat wavelength dispersion (Re(450)=Re(550)=Re(650)).
[0120] In one or more embodiments, the first retardation layer may have an in-plane retardation short wavelength dispersion (Re(450) / Re(550)) in the range of 0.9 to 1.1 and an in-plane retardation long wavelength dispersion (Re(650) / Re(550)) in the range of 0.9 to 1.1. Within these ranges, the first retardation layer can suppress lateral light leakage while reducing brightness in black mode. In an embodiment, the first retardation layer has an in-plane retardation short wavelength dispersion in the range of 1.001 to 1.009 and an in-plane retardation long wavelength dispersion in the range of 0.98 to 1.0.
[0121] In one or more embodiments, the first retardation layer may have an Re of 100 nm to 165 nm (e.g., 105 nm to 163 nm) at a wavelength of 450 nm, and an Re of 95 nm to 155 nm (e.g., 96 nm to 153 nm) at a wavelength of 650 nm. Within these ranges, the first retardation layer may (e.g., easily) achieve short wavelength dispersion and long wavelength dispersion within the above ranges.
[0122] The first retarder layer may have a total light transmittance of 90% or more (eg, 90% to 100%) and a haze of 0.3% or less (eg, 0% to 0.3%, or 0.1% to 0.3%). Within these ranges, the first retarder layer may be used in a retarder layer stack.
[0123] The first retardation layer may have a thickness of 70 micrometers or less, for example, greater than 0 micrometers and less than or equal to 70 micrometers, for example, 20 micrometers to 70 micrometers, or 20 micrometers to 50 micrometers. Within these ranges, the first retardation layer can be used for a polarizing plate.
[0124] The first retardation layer is a non-liquid crystal film, which may include a stretched film formed of an optically transparent resin. The non-liquid crystal film may refer to a film that is not formed of at least one of a liquid crystal monomer, a liquid crystal oligomer, or a liquid crystal polymer, or a film formed of a material that will not be converted into a liquid crystal monomer, a liquid crystal oligomer, or a liquid crystal polymer by light irradiation or the like. In other words, the first retardation layer is a non-liquid crystal film and does not contain any liquid crystal monomer, liquid crystal oligomer, and / or liquid crystal polymer, and does not contain any material that can be converted into a liquid crystal monomer, a liquid crystal oligomer, and / or a liquid crystal polymer by light irradiation and / or the like.
[0125] For example, the first delay layer may be a film formed by at least one resin selected from cellulose resins, including triacetyl cellulose and the like; polyester resins, including polyethylene terephthalate (PET), polybutylene terephthalate, polyethylene naphthalate and polybutylene naphthalate; cyclic olefin copolymer (COC) resin; cyclic olefin polymer (COP) resin; polycarbonate resin; polyether sulfone resin; polysulfone resin; polyamide resin; polyimide resin; polyolefin resin; polyarylate resin; polyvinyl alcohol resin; polyvinyl chloride resin; polyvinylidene chloride resin; and acrylic resin.
[0126] In one or more embodiments, the first retardation layer includes a cyclic olefin polymer (COP) or a cyclic olefin copolymer (COC) film. In one or more embodiments, the cyclic olefin polymer (COP) film can be applied to a polarizing plate of an IPS or FFS mode liquid crystal display to promote improved contrast and viewing angle while improving color change.
[0127] The first delay layer may be a hydrophobic film. In one or more embodiments, the first delay layer may include a film formed by a resin having positive intrinsic birefringence. For example, the first delay layer may include at least one selected from a cycloolefin polymer (COP) film, a cycloolefin polymer (COC) film, and a cycloolefin polymer (COP) film.
[0128] The first retardation layer may have a thickness of 1 g / m 2 / day or higher (e.g., 1 g / m 2 / day to 30g / m 2 / day, or 1g / m 2 / day to 10g / m 2 Within these ranges, the first retardation layer can contribute to improving the durability of the polarizing plate under high temperature / high humidity or high temperature conditions.
[0129] The first retardation layer may have a glass transition temperature of 130° C. or more, for example, 130° C. to 200° C. Within these ranges, the first retardation layer may contribute to improving durability of the polarizing plate under high temperature / high humidity or high temperature conditions.
[0130] The first delay layer may be an unstretched film of the first delay layer uniaxially stretched in the longitudinal direction (machine direction; MD) or the transverse direction (traverse direction; TD), or a film prepared by uniaxially stretching the unstretched film in a direction oblique to the MD. In an embodiment, the first delay layer is a film prepared by uniaxially stretching the unstretched film of the first delay layer in MD. The stretching conditions, such as the stretching ratio, the stretching temperature, the stretching method, etc., can be adjusted to provide the above-mentioned Re range at a wavelength of 550nm. The unstretched film of the first delay layer can be prepared by melt extrusion or solvent casting of the composition for the first delay layer, but is not limited thereto. Both melt extrusion and solvent casting can be carried out under appropriate conditions (e.g., conditions known to those skilled in the art).
[0131] The first retardation layer has a slow axis and a fast axis in its in-plane direction, wherein the slow axis of the first retardation layer may be substantially parallel to the light absorption axis of the polarizer. For example, assuming that the light absorption axis of the polarizer is 0°, the slow axis of the first retardation layer may be tilted at an angle of -5° to 5° relative to the light absorption axis of the polarizer. In an embodiment, the slow axis of the first retardation layer is tilted at an angle of -0.5° to 0.5°, or -0.1° to 0.1°. Within these ranges, the contrast can be enhanced (e.g., easily) and the field of view can be expanded, and color changes can be minimized or reduced.
[0132] Second delay layer
[0133] The second retardation layer is a +C layer (nz>nx≒ny). If (for example, when) combined with the first retardation layer as a +A layer, the second retardation layer can be applied to IPS or FFS mode liquid crystal displays to promote contrast enhancement and expand the viewing angle while minimizing or reducing color changes.
[0134] The second retardation layer may have an Rth of -110nm to -50nm at a wavelength of 550nm. Within these ranges, the second retardation layer can be applied to a liquid crystal display to promote contrast enhancement and an expansion of the viewing angle while minimizing or reducing color changes. In an embodiment, the second retardation layer has an Rth of -110nm to -60nm at a wavelength of 550nm, for example -110nm to -75nm.
[0135] The second retardation layer may have Re of 10 nm or less, for example, Re of 0 nm to 10 nm, at a wavelength of 550 nm. Within these ranges, the second retardation layer may (for example, easily) achieve the above Rth range.
[0136] The second retardation layer may have a positive wavelength dispersion or a flat wavelength dispersion for Re and Rth. In one or more embodiments, the second retardation layer may satisfy the following relations 2 and 3. In these cases, the contrast ratio may be enhanced and the viewing angle may be expanded (e.g., easily) while minimizing or reducing color changes.
[0137] 1.0≤Re2(450) / Re2(550)≤1.1 --- (2)
[0138] 1.0≤Rth2(450) / Rth2(550)≤1.1 --- (3)
[0139] where Re2(450) and Re2(550) are the in-plane retardation of the second retardation layer at wavelengths of 450 nm and 550 nm, respectively (unit: nm), and
[0140] Rth2(450) and Rth2(550) are the out-of-plane retardations of the second retardation layer at wavelengths of 450 nm and 550 nm, respectively (unit: nm).
[0141] The second retarder layer can have a total light transmittance of 90% or more (eg, 90% to 100%) and a haze of 1% or less (eg, 0% to 0.8%, or 0.1% to 0.7%). Within these ranges, the second retarder layer can be used in a retarder layer stack.
[0142] The second retardation layer may have a thickness of 10 μm or less (eg, greater than 0 μm and less than or equal to 10 μm, eg, 2 μm to 8 μm), within these ranges the second retardation layer may ensure a reduced thickness of the retardation layer stack.
[0143] The second retardation layer has a lower refractive index than the first retardation layer, and may have a refractive index of 1 to 2, for example, 1.4 to 1.6, or 1.5 to 1.6.
[0144] The second retardation layer may have a thickness of 1 g / m 2 / day or higher (e.g., 1 g / m 2 / day to 50g / m 2 Within these ranges, the second retardation layer can promote improved durability of the polarizer under high temperature / high humidity or high temperature conditions.
[0145] The second retardation layer may have a glass transition temperature of 130° C. or higher (eg, 130° C. to 200° C.) Within these ranges, the second retardation layer may promote improved durability of the polarizer under high temperature / high humidity or high temperature conditions.
[0146] The second retardation layer may be formed of a material different from that of the first retardation layer, and may be formed of a hydrophobic material having a different birefringence from that of the first retardation layer and having a negative intrinsic birefringence.
[0147] The second retardation layer may be a non-liquid crystal layer. That is, the second retardation layer is a non-liquid crystal film and does not contain any liquid crystal monomer, liquid crystal oligomer and / or liquid crystal polymer, and does not contain any material that can be converted into a liquid crystal monomer, liquid crystal oligomer and / or liquid crystal polymer by light irradiation and / or similar means. With this structure, the polarizer can show further improved durability after being placed under high temperature / high humidity or high temperature conditions for a long time.
[0148] The second delay layer may include at least one of a cellulose compound or a polystyrene compound as a main component. "Compound" may refer to a polymer and / or an oligomer. In one or more embodiments, each of the cellulose compound and the polystyrene compound may further contain a halogen (e.g., as a substituent). The halogen may include fluorine, chlorine, iodine, or bromine. In an embodiment, the cellulose compound and the polystyrene compound may each further contain fluorine. Here, "main component" refers to a component present in the second delay layer in an amount of 90wt% or more (e.g., 95wt% or more) based on the total amount 100wt% of the second delay layer.
[0149] The resin with negative intrinsic birefringence may include a polymer with negative intrinsic birefringence. The polymer with negative intrinsic birefringence may include at least one selected from, for example, the following: a homopolymer of styrene or a styrene derivative, a polystyrene polymer including a copolymer of styrene or a styrene derivative and a comonomer, a polyacrylonitrile polymer, a poly(methyl methacrylate) copolymer, and a cellulose copolymer including cellulose esters, cellulose ethers and / or the like. The comonomer may include at least one selected from acrylonitrile, maleic anhydride, methyl methacrylate and butadiene. For example, the second delay layer may include at least one polystyrene copolymer or a cellulose copolymer. In an embodiment, the second delay layer may include a polystyrene copolymer.
[0150] In one or more embodiments, the cellulose copolymer may include a repeating unit represented by Formula 1. The cellulose copolymer may include a cellulose ester polymer including one or more units in which at least some of the hydrogen atoms of a hydroxyl (OH) group (e.g., a C2 hydroxyl group, a C3 hydroxyl group, or a C6 hydroxyl group shown in Formula 1) of a sugar monomer constituting cellulose are substituted with an acyl group. Here, the acyl group may be substituted or unsubstituted.
[0151] [Formula 1]
[0152]
[0153] Wherein n is an integer of 1 or greater.
[0154] The polystyrene compound may include a moiety represented by Formula 2.
[0155] [Formula 2]
[0156]
[0157] in It is the attachment site of the element;
[0158] R 1 , R 2 and R 3are each independently a hydrogen atom, an alkyl group, a substituted alkyl group or a halogen;
[0159] n R are each independently alkyl, substituted alkyl, halogen, hydroxy, carboxyl, nitro, alkoxy, amino, sulfonic acid, phosphoric acid, acyl, acyloxy, phenyl, alkoxycarbonyl or cyano, R 1 , R 2 or R 3 At least one of is halogen and / or at least one R is halogen; and
[0160] n is an integer of 0-5.
[0161] The composition for the second retardation layer may further include a halogen-free styrene polymer, for example, polystyrene.
[0162] The composition for the second delay layer may further include an additive. The additive is used to adjust the wavelength dispersion. The additive with aromatic condensed rings may include 2-naphthyl benzoate, anthracene, phenanthrene, 2,6-naphthalene dicarboxylic acid diester and / or the like. The content of the additive with aromatic condensed rings in the composition for the second delay layer may be 0.1wt% to 30wt%, such as 1wt% to 10wt%. Within these ranges, the composition for the second delay layer can control delay (e.g., delay performance) and wavelength dispersion.
[0163] The composition for the second retardation layer may further include appropriate additives (such as additives known to those skilled in the art). The additives may include pigments, antioxidants, antistatic agents, thermal stabilizers and / or the like, but are not limited thereto.
[0164] The second delay layer can be a cured product of the composition, for example, a thermally cured or photocured product of the composition. The second delay layer can be a cured coating of the composition by thermal curing or photocuring, and can be formed by any appropriate method (e.g., a method known to those skilled in the art).
[0165] The retardation layer stack may have an out-of-plane retardation of -40 nm to less than 0 nm at a wavelength of 550 nm, and may satisfy Relation 4. Therefore, the retardation layer stack may promote improvement in front contrast, and may reduce light leakage and color variation on the side while ensuring good clarity and a good viewing angle on a black screen.
[0166] 1.1≤Rth(450) / Rth(550)≤1.5, --- (4)
[0167] where Rth(450) and Rth(550) are the out-of-plane retardations of the retardation layer stack at wavelengths of 450 nm and 550 nm, respectively (in nanometers).
[0168] In an embodiment, the retardation layer stack has an Rth(550) of -25 nm to -5 nm, -25 nm to -10 nm, or -20 nm to -10 nm.
[0169] In an embodiment, in Relation 4, Rth(450) / Rth(550) is 1.15 to 1.5, for example, 1.2 to 1.4.
[0170] In one or more embodiments, similar to Rth(550), Rth(450) may be a negative value. For example, Rth(450) may be from -20 nm to -5 nm, or from -12 nm to -7 nm. Within these ranges, the delay layer stack may satisfy (e.g., easily achieve) Relation 1.
[0171] The retardation layer stacking can further satisfy Relation 5. Therefore, the retardation layer stacking can promote the improvement of the front contrast ratio, and can reduce the light leakage and color change on the side while ensuring good clarity and good viewing angle on the black screen.
[0172] 0.1≤Rth(650) / Rth(550)≤1.0, --- (5)
[0173] where Rth(650) and Rth(550) are the out-of-plane retardations of the retardation layer stack at wavelengths of 650 nm and 550 nm, respectively (in nanometers).
[0174] In an embodiment, in Relation 5, Rth(650) / Rth(550) may be from 0.2 to 1.0, for example, from 0.5 to 0.9.
[0175] In one or more embodiments, similar to Rth(550), Rth(650) may be a negative value. For example, Rth(650) may be from -20 nm to -1 nm, or from -13 nm to -5 nm. Within these ranges, the delay layer stack may (e.g., easily) achieve Relation 2.
[0176] In one or more embodiments, the delay layer stack may satisfy Equation 6 and Equation 7. Therefore, the effect of the present disclosure may be achieved (eg, easily achieved).
[0177] Rth(450) / Rth(550) > Re(450) / Re(550), --- (6)
[0178] Re(650) / Re(550) > Rth(650) / Rth(550), --- (7)
[0179] where Re(450), Re(550), and Re(650) are the in-plane retardations (in nanometers) of the retarder stack at wavelengths of 450 nm, 550 nm, and 650 nm, respectively; and
[0180] Rth(450), Rth(550), and Rth(650) are the out-of-plane retardations (in nanometers) of the retarder stack at wavelengths of 450 nm, 550 nm, and 650 nm, respectively.
[0181] In one or more embodiments, the retarder stack may have positive wavelength dispersion and may satisfy the relationships: 1 < Re(450) / Re(550) ≤ 1.1 and 0.9 ≤ Re(650) / Re(550) < 1. For example, Re(450) / Re(550) may range from 1.001 to 1.05, and Re(650) / Re(550) may range from 0.9 to 0.99.
[0182] The retarder stack may have a thickness of 45 μm to 90 μm, such as 40 μm to 85 μm, or 40 μm to 80 μm. Within these ranges, the retarder stack can be used for a polarizer.
[0183] Polarizer
[0184] The polarizer is used to reduce color reflection and reflectance over the entire field of view angle by linearly polarizing external light or light incident from the retarder stack.
[0185] The polarizer may have a polarization degree of 99% or higher and a single light transmittance (Ts) of 42% or higher. By simultaneously (e.g., together) satisfying the polarization degree and the single light transmittance, the reflectance can be significantly reduced if (e.g., when) the polarizer is stacked on the retarder stack. "Single light transmittance" refers to the single light transmittance (Ts) measured in the visible light region (e.g., at wavelengths from 400 nm to 700 nm) and can be measured by an appropriate method (e.g., a method known to those skilled in the art). The "polarization degree" can be measured by any appropriate method (e.g., a method known in the present technology). For example, the polarizer may have a polarization degree of 99% to 99.9999% and a single light transmittance of 42% to 50%.
[0186] When a polarizer is manufactured using a polyvinyl alcohol film, the light absorption axis of the polarizer can be the stretching direction of the polyvinyl alcohol film, such as the longitudinal direction (machine direction; MD) of the polarizer. The polarizer may include a polyvinyl alcohol-based polarizer manufactured by uniaxial stretching of a polyvinyl alcohol film. In one or more embodiments, the polarizer may be manufactured by dyeing, stretching, cross-linking and color correction of the polyvinyl alcohol film. By appropriately changing the conditions of the dyeing, stretching, cross-linking and color correction processes, a polarizer having both the above-mentioned polarization degree and light transmittance can be achieved. The polarizer may have a thickness of 5 microns to 40 microns. Within these ranges, the polarizer can be used for the polarizer.
[0187] The polarizer may include, in addition to the retardation layer stack, at least one protective layer as described below.
[0188] In one or more embodiments, a protective layer may be stacked on the other surface of the polarizer.
[0189] Protective layer
[0190] The protective layer may be stacked on the upper surface of the polarizer to protect the polarizer. The protective layer may protect the polarizer to improve the reliability and mechanical strength of the polarizer. The protective layer may be omitted. The protective layer may be stacked on the upper surface of the polarizer in a single layer or multiple layers. The protective layer may be omitted as long as the mechanical properties of the polarizer can be guaranteed without the protective layer. The protective layer may include at least one optically transparent protective film or protective coating. The protective film may include a film formed of at least one selected from the following: cellulose ester resin, including triacetylcellulose (TAC) and / or the like; cyclic polyolefin resin, such as amorphous cyclic polyolefin (COP) and / or the like; polycarbonate resin; polyester resin, such as polyethylene terephthalate (PET) and / or the like; polyether sulfone resin; polysulfone resin; polyamide resin; polyimide resin; non-cyclic polyolefin resin; poly(meth)acrylate resin, including poly(methyl methacrylate) and / or the like; polyvinyl alcohol resin; polyvinyl chloride resin; and polyvinylidene chloride resin, but is not limited thereto.
[0191] The protective coating may be formed of an actinic radiation curable resin composition including an actinic radiation curable compound and a polymerization initiator. The actinic radiation curable compound may include at least one selected from the group consisting of a cation polymerization curable compound, a free radical polymerization curable compound, a urethane resin, and a silicone resin.
[0192] The protective layer can be a non-retarding film or have an in-plane retardation within a set or predetermined range. For example, at a wavelength of 550 nanometers, the protective layer can have an in-plane retardation of less than 5,000 nanometers, or 5,000 nanometers or greater, 120 nanometers to 160 nanometers, or 5 nanometers to 0 nanometers. Within these ranges, the protective layer can protect the polarizer without compromising the effect of the retardation layer stack.
[0193] The protective layer may have a thickness of 10 micrometers or less, 5 micrometers to 300 micrometers, 5 micrometers or less, or 5 micrometers to 200 micrometers. Within these ranges, the protective layer can be used for the polarizer.
[0194] A functional coating layer may be further formed on the upper surface of the protective layer. The functional coating layer may include at least one selected from a hard coating layer, an anti-fingerprint layer, an anti-reflection layer, an anti-glare layer, a low reflection layer, and an ultra-low reflection layer.
[0195] In one or more embodiments, the protective layer has a low water vapor permeability to further improve the durability of the polarizer after being subjected to high temperature and high humidity conditions. For example, the protective layer can have a water vapor permeability of 100 g / m2 / day or less, for example, 1 g / m2 / day to 100 g / m2 / day. Within these ranges, the polarizer can exhibit good durability and the protective layer can be (e.g., easily) manufactured.
[0196] At least one protective layer, adhesive layer or bonding layer may be further disposed between the polarizer and the retardation layer stack and / or on the lower surface of the retardation layer stack.
[0197] The protective layer is substantially the same as described above.
[0198] Here, the protective layer stacked on the upper surface of the polarizer may be referred to as a first protective layer, the protective layer inserted between the polarizer and the delay layer stack may be referred to as a second protective layer, and the protective layer stacked on the lower surface of the delay layer stack may be referred to as a third protective layer.
[0199] The second adhesive layer may be further disposed between the polarizer and the delay layer stack. The second adhesive layer may attach the delay layer stack to the polarizer. Alternatively, the second adhesive layer may attach the protective layer stacked on the polarizer to the delay layer stack.
[0200] The second adhesive layer may be an adhesive layer having a modulus at 25° C. lower than that of the first adhesive layer at 25° C. By stacking the second adhesive layer having a lower modulus at 25° C. on the upper surface of the second delay layer and stacking the first adhesive layer having a relatively higher modulus at 25° C. on the lower surface of the second delay layer, the polarizer may further improve impact resistance if (for example, when) an external impact is applied to the polarizer.
[0201] A third adhesive layer may be further stacked on a lower surface of the retardation layer stack. The third adhesive layer may attach the polarizer to the panel.
[0202] Each of the second adhesive layer and the third adhesive layer may be formed by a composition comprising at least one adhesive resin selected from (meth) acrylic resin, epoxy resin, epoxy (meth) acrylic resin, urethane resin, urethane (meth) acrylic resin and silicone resin. For example, the second adhesive layer and the third adhesive layer may include at least one of a thermally cured product of the composition or a photocured product of the composition.
[0203] Each of the second adhesive layer and the third adhesive layer can be a pressure-sensitive adhesive layer. Each of the composition for the second adhesive layer and the composition for the third adhesive layer can include (meth) acrylic resin as described above. These compositions can further include a curing agent. The composition can further include an additive.
[0204] Figures 1 to 3 is a cross-sectional view of a polarizing plate according to an embodiment of the present disclosure. Figures 1 to 3 In the present invention, the “upper surface” of the polarizer refers to the light exiting surface of the polarizer, and the “lower surface” of the polarizer refers to the light incident surface of the polarizer.
[0205] According to one or more embodiments, the polarizing plate may include a polarizer 100, a first protective layer 300 formed on the upper surface of the polarizer 100, and a second adhesive layer 400 and a delay layer stack sequentially stacked on the lower surface of the polarizer 100, wherein the delay layer stack may include a second delay layer 220, a first adhesive layer 230 and a first delay layer 210 sequentially stacked starting from the polarizer 100.
[0206] According to another embodiment, a polarizing plate may include a polarizer 100, a first protective layer 300 formed on an upper surface of the polarizer 100, and a second protective layer 500, a second adhesive layer 400 and a delay layer stack sequentially stacked on a lower surface of the polarizer 100, wherein the delay layer stack may include a second delay layer 220, a first adhesive layer 230 and a first delay layer 210 stacked sequentially starting from the polarizer 100.
[0207] According to a further embodiment, the polarizing plate includes a polarizer 100, a first protective layer 300 formed on the upper surface of the polarizer 100, and a second protective layer 500, a second adhesive layer 400, a delay layer stack and a third adhesive layer 600 sequentially stacked on the lower surface of the polarizer 100, wherein the delay layer stack may include a second delay layer 220, a first adhesive layer 230 and a first delay layer 210 sequentially stacked starting from the polarizer 100.
[0208] Optical display device
[0209] According to one or more embodiments, the optical display device includes the polarizing plate. The optical display device may include a liquid crystal display. The polarizing plate may be included as an observer-side polarizing plate of the optical display device. In one or more embodiments, the liquid crystal display may be an IPS or FFS mode liquid crystal display.
[0210] The liquid crystal display may include a liquid crystal panel, an observer-side polarizing plate disposed on one surface of the liquid crystal panel, and a light source-side polarizing plate disposed on another surface (e.g., facing away from the one surface) of the liquid crystal panel. The light absorption axis of the polarizer of the observer-side polarizing plate may be substantially orthogonal to the light absorption axis of the light source-side polarizing plate.
[0211] In one or more embodiments, the liquid crystal display may include a liquid crystal panel, an observer-side polarizing plate disposed on one surface of the liquid crystal panel, and a light source-side polarizing plate disposed on another surface of the liquid crystal panel (e.g., facing or facing away from the one surface). The observer-side polarizing plate may include a first retardation layer, a second retardation layer, a polarizer, and a protective layer stacked sequentially from the liquid crystal panel. The light source-side polarizing plate may include a protective layer, a polarizer, and a protective layer stacked sequentially from the liquid crystal panel. Here, the light absorption axis (e.g., 0°) of the polarizer of the observer-side polarizing plate is substantially parallel to the slow axis (e.g., 0°) of the first retardation layer. The light absorption axis of the polarizer of the observer-side polarizing plate is substantially orthogonal to the liquid crystal arrangement direction (e.g., 90°) of the liquid crystal panel and the light absorption axis (e.g., 90°) of the polarizer of the light source-side polarizing plate, respectively.
[0212] In one or more embodiments, the liquid crystal display may include a liquid crystal panel, an observer-side polarizing plate disposed on one surface of the liquid crystal panel, and a light source-side polarizing plate disposed on another surface of the liquid crystal panel (e.g., facing or facing away from the one surface). The light source-side polarizer may include a first delay layer, a second delay layer, a polarizer, and a protective layer stacked sequentially from the liquid crystal panel. The observer-side polarizing plate may include a protective layer, a polarizer, and a protective layer stacked sequentially from the liquid crystal panel. Here, the light absorption axis (e.g., 0°) of the polarizer of the light source-side polarizing plate is substantially parallel to the slow axis (e.g., 0°) of the first delay layer. The light absorption axis of the polarizer of the light source-side polarizing plate is substantially orthogonal to the liquid crystal arrangement direction (e.g., 90°) of the liquid crystal panel and the light absorption axis (e.g., 90°) of the polarizer of the observer-side polarizing plate, respectively.
[0213] Next, the present disclosure will be described in more detail with reference to some examples. However, it should be noted that these examples are provided for illustrative purposes only and should not be interpreted as limiting the present disclosure in any way.
[0214] Example 1
[0215] A polarizer (light transmittance: 44%, thickness: 10 μm) was prepared by dyeing a polyvinyl alcohol film (pre-stretched thickness: 60 μm, Kuraray Co., Ltd., Japan) in an iodine aqueous solution at 55°C and then uniaxially stretching the polyvinyl alcohol film to 6 times the initial length in the MD direction of the film.
[0216] The first retardation layer (+A layer, Re: positive wavelength dispersion, thickness: 45 nm) was prepared by stretching a cycloolefin polymer (COP) film (ZF, Zeon Co., Ltd., Japan) in the MD direction of the film to 2.3 times the original length at 140°C.
[0217] A second delay layer (non-liquid crystal layer, +C layer, thickness: 3 μm, Tg: 140°C, moisture permeability: 30 g / m2·day) was prepared by dissolving a fluorine-substituted polystyrene copolymer composition (VM, Eastman Company) in methyl ethyl ketone, coating the resulting mixture on one surface of a release PET film, drying the composition, and removing the release PET film.
[0218] By bonding the second retardation layer to the upper surface of the first retardation layer through the first adhesive layer, a retardation layer stack of first retardation layer / first adhesive layer / second retardation layer was prepared.
[0219] Polyethylene terephthalate (PET) film (DSG, DNP company) is stacked on the upper surface of polarizer as the first protective layer, and cycloolefin polymer (COP) film (ZF, Japan Ruiong company) is stacked on the lower surface of polarizer as the second protective layer. Then, the +C layer stacked by the second adhesive layer is stacked on the lower surface of cycloolefin polymer (COP) film, so as to prepare a polarizing plate including PET film / polarizer / COP film / second adhesive layer / second retardation layer / first adhesive layer / first retardation layer stacking structure. The slow axis of the first retardation layer is tilted at an angle of 0.1 ° relative to the light absorption axis (MD of polarizer) of the polarizer.
[0220] The first adhesive layer is formed by a composition prepared by adding a solvent to a mixture, the mixture including 100 parts by weight of an acrylic resin solution (SZ7523, an ethyl acetate solution containing an acrylic ester copolymer), 3.1 parts by weight of BXX-4805 (a toluene and methyl ethyl ketone solution containing a metal acetylacetone complex salt), and 14.5 parts by weight of BXX-6460 (an ethyl acetate solution containing toluene diisocyanate) as a curing agent solution, and 0.08 parts by weight of BXX-6342 (containing 98% by weight of a silane compound) as an additive. In terms of solid content, the acrylic resin solution contains 100 parts by weight of an acrylic resin, 0.31 parts by weight of a metal acetylacetone complex salt, 1.45 parts by weight of toluene diisocyanate, and 0.0784 parts by weight of a silane compound. The first adhesive layer is formed by depositing the composition onto a release film to form a set or predetermined thickness, heat treating at 30°C for 3 hours, and peeling the resulting film from the release film, and the thickness is 6.5 microns.
[0221] The second adhesive layer is a (meth)acrylic adhesive film having a lower storage modulus at 25° C. than that of the first adhesive layer.
[0222] Examples 2 to 4
[0223] A polarizing plate was prepared in substantially the same manner as in Example 1, except that the thickness of the first adhesive layer and the content (eg, amount) of each component in the first adhesive layer composition were changed to change the modulus of the first adhesive layer.
[0224] Comparative Examples 1 to 4
[0225] A polarizing plate was prepared in substantially the same manner as in Example 1, except that the thickness of the first adhesive layer and the content (eg, amount) of each component in the first adhesive layer composition were changed to change the modulus of the first adhesive layer.
[0226] Reference Example 1
[0227] The first retardation layer (+A layer, Re: positive wavelength dispersion, thickness: 45 μm) was prepared by stretching a cycloolefin polymer (COP) film (ZF, Zeon) in the MD direction of the film to 2.3 times the original length at 140°C.
[0228] The second retardation layer (non-liquid crystal layer, +C layer, thickness: 4 μm, Tg: 140°C, moisture permeability: 30 g / m2) formed on one surface of the first retardation layer was prepared by dissolving a fluorine-substituted polystyrene-containing copolymer composition (VM, Eastman Company) in methyl ethyl ketone and coating the composition on one surface of the first retardation layer, followed by drying. 2 · days) of delay layer stacking.
[0229] A polarizing plate including a stack structure of PET film / polarizer / COP film / second adhesive layer / second retardation layer / first retardation layer was manufactured in the same manner as in Example 1 using the retardation layer stack.
[0230] The retardation of each of the retardation layer stack, the first retardation layer and the second retardation layer was measured using Axoscan (Axometry).
[0231] (1) High temperature and high humidity durability (unit: none): Samples were prepared by cutting each polarizing plate into a size of 10 cm×10 cm (length×width). The samples were stored in an environmental chamber at 60°C and 90% RH for 250 hours, and then it was evaluated whether the first retardation layer and the second retardation layer were peeled off if (for example, when) the first retardation layer and the second retardation layer were pulled manually.
[0232] ◎: There is no peeling between the first retardation layer and the second retardation layer.
[0233] ○: A considerable force is required for the peeling of the first retardation layer and the second retardation layer.
[0234] Δ: A slight force is required for the peeling of the first retardation layer and the second retardation layer.
[0235] ×: The first retardation layer and the second retardation layer are very easily peeled off.
[0236] (2) Impact resistance (unit: cm): The impact resistance was evaluated by the falling ball method. For example, the polarizing plate was cut into polarizing plate samples of 200 mm × 35 mm (length × width) to prepare Figure 4 Impact resistance evaluation sample with the cross section shown. Figure 4 The sample is prepared by placing two second supports 2 (width×length×thickness=45mm×35mm×10mm) on the first support 1 so as to be spaced apart from each other, stacking soda lime glass 3 (width×length×thickness=200mm×35mm×1.2cm) on the second support 2, and stacking the cut polarizing plate sample 4 on the soda lime glass 3.
[0237] Reference Figure 4 , a ball (spherical, cross-sectional diameter: 2 mm, weight: 44 g) was dropped vertically from a set or predetermined height onto the upper surface at the front center of the cut polarizing plate sample 4. The ball was dropped in such a manner that the vertical drop distance of the ball was sequentially increased from 150 mm to 200 mm and then to 250 mm. The cut polarizing plate samples and soda lime glass were observed with the naked eye and evaluated according to the following criteria. The presence of cracks and / or breaks was evaluated with the naked eye.
[0238] ◎: There are no cracks and breaks in the +C layer of the cut polarizing plate sample.
[0239] ○: Slight cracks and breaks exist in the +C layer of the cut polarizing plate sample, which are difficult to be recognized with the naked eye.
[0240] Δ: Cracks and breaks visible to the naked eye exist in the +C layer of the cut polarizing plate sample.
[0241] ×: Cracks and breaks that are easily visible to the naked eye exist in the +C layer of the cut polarizing plate sample.
[0242] (3) Bending: Each polarizing plate was cut into a size of 10 cm × 10 cm (length × width) and bent to a curvature radius of 2 mm so that the retardation layer stacking side of the polarizing plate was located on the outside. The absence of cracks and / or peeling of the retardation layer stacking was evaluated as ○, and any cracks and / or peeling was evaluated as ×.
[0243] (4) Color change (unit: none): The polarizing plate of each embodiment and comparative example was used instead of the polarizing plate on the viewing side of a 55-inch TV, and the TV was operated (e.g., turned on). The color coordinate distance between the color coordinates (60°, 45°) and (60°, 135°) was measured in the color coordinate system (x, y). A lower color coordinate distance indicates a smaller color change on the side.
[0244] Table 1
[0245]
[0246] Table 2
[0247]
[0248] As shown in Table 1, the polarizing plate of the present disclosure has good durability and reliability after being placed at high temperature / high humidity or high temperature for a long time, good impact resistance and bending performance, good front contrast, low brightness in black mode to reduce light leakage, and color change on the side.
[0249] As shown in Table 2, the polarizing plates of the comparative examples fail to achieve all the advantageous or desired effects of the present disclosure.
[0250] As used herein, the terms "use", "in use", and "used" may be considered synonymous with the terms "utilize", "utilizing", and "utilized", respectively. As used herein, when expressions such as "at least one", "one", and "selected from" precede a list of elements, they modify the entire list of elements rather than modifying individual elements in the list. For example, "selected from at least one of a, b, and c", "at least one of a, b, or c", and "at least one of a, b, and / or c" may mean only a, only b, only c, a and b (e.g., simultaneously), a and c (e.g., simultaneously), b and c (e.g., simultaneously), all of a, b, and c, or variations thereof.
[0251] The use of “may” when describing embodiments of the present inventive concept means “one or more embodiments of the present inventive concept”.
[0252] In addition, any numerical range mentioned herein is intended to include all sub-ranges of the same numerical precision contained in the range. For example, the range of "1.0 to 10.0" is intended to include all sub-ranges between (and including) the minimum value 1.0 and the maximum value 10.0, i.e., having a minimum value equal to or greater than 1.0 and a maximum value equal to or less than 10.0, such as 2.4 to 7.6. Any maximum numerical limit mentioned herein is intended to include all lower numerical limits contained therein, and any minimum numerical limit mentioned in this specification is intended to include all higher numerical limits contained therein. Therefore, the applicant reserves the right to modify this specification (including claims) to expressly state any sub-range contained in the range explicitly mentioned herein.
[0253] Here, unless otherwise defined, steps, tasks, or actions listed in a particular order should not necessarily mean that the invention or claims require that particular order. That is, as a general rule, unless the steps, tasks, or actions of a method (e.g., a method claim) actually specify an order, these steps, tasks, or actions should not be interpreted as requiring a particular order.
[0254] It should be understood that those skilled in the art can make various modifications, changes, variations and equivalent embodiments to the present disclosure without departing from the spirit and scope of the present disclosure.
Claims
1. A polarizing plate, comprising: a polarizer having a first surface and a second surface facing the first surface; as well as a retardation layer stack disposed on the first surface of the polarizer, wherein the retardation layer stack comprises a second retardation layer, a first adhesive layer and a first retardation layer stacked in sequence from the first surface of the polarizer, The storage modulus of the first adhesive layer at 25°C is 1×10 5 Pa to 1×10 6 Pa, and The second retardation layer and the first adhesive layer satisfy Relation 1: Relationship 1 0.3≤T2 / T1≤1.0 where T1 is the thickness of the first adhesive layer in micrometers, and T2 is the thickness of the second retardation layer in micrometers. 2 . The polarizing plate according to claim 1 , wherein the first adhesive layer has a thickness of 13 μm or less. 3 . The polarizing plate according to claim 1 , wherein the second retardation layer has a thickness of 10 μm or less.
4. The polarizing plate according to claim 1, wherein the storage modulus of the first adhesive layer at 60°C is 6×10 4 Pa to 8×10 5 Pa. 5 . The polarizing plate of claim 1 , wherein a ratio of a storage modulus of the first adhesive layer at 25° C. to a storage modulus at 60° C. is 1.25:1 to 1.6:
1. The polarizing plate according to claim 1 , wherein the first adhesive layer has a glass transition temperature of −10° C. or less. The polarizing plate according to claim 1 , wherein the first adhesive layer is a pressure-sensitive adhesive layer. 8 . The polarizing plate of claim 1 , wherein the first adhesive layer comprises a thermally cured product of a composition comprising a (meth)acrylic resin and a curing agent.
9. The polarizing plate according to claim 8, wherein the (meth)acrylic resin comprises a (meth)acrylic copolymer of a monomer mixture, the monomer mixture comprises a (meth)acrylic monomer containing an alkyl group and a (meth)acrylic monomer containing a crosslinkable functional group, and the curing agent comprises at least one curing agent selected from the group consisting of an isocyanate curing agent, a metal chelate curing agent, an aziridine curing agent, an epoxy curing agent and a carbodiimide curing agent. 10 . The polarizing plate according to claim 1 , wherein the second retardation layer is a non-liquid crystal layer. 11 . The polarizing plate according to claim 10 , wherein the second retardation layer includes at least one of a cellulose-based compound or a polystyrene-based compound as a main component. 12 . The polarizing plate according to claim 11 , wherein each of the cellulose-based compound and the polystyrene-based compound contains a halogen. 13 . The polarizing plate according to claim 1 , wherein the first retardation layer is a hydrophobic non-liquid crystal film. 14 . The polarizing plate of claim 13 , wherein the first retardation layer comprises a cyclic olefin polymer film or a cyclic olefin copolymer film. 15 . The polarizing plate of claim 1 , wherein the first adhesive layer is directly on each of the first retardation layer and the second retardation layer. 16 . The polarizing plate according to claim 1 , wherein the first retardation layer is a +A layer, and the second retardation layer is a +C layer.
17. The polarizing plate according to claim 1, further comprising: a first protective layer disposed on the second surface of the polarizer, and The first protective layer has a thickness of 100 g / m 2 / day or less moisture penetration rate.
18. The polarizing plate according to claim 1, further comprising: A second adhesive layer is disposed between the retardation layer stack and the polarizer. 19 . The polarizing plate of claim 18 , wherein a storage modulus of the second adhesive layer at 25° C. is lower than the storage modulus of the first adhesive layer at 25° C.
20. An optical display device comprising the polarizing plate according to claim 1.
Citation Information
Patent Citations
Anti-reflection circularly polarizing plate for organic EL display and organic EL display
KR1020130103595A
Multi-diameter clipping mechanism
KR1020230148104A